EFEKTIVITAS JUS MENTIMUN UNTUK MENURUNKAN TEKANAN DARAH TERHADAP KELUARGA - Devia Nurafnisa; Nina Pamela Sari (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Hypertension, commonly referred to as high blood pressure, is a long-term health concern that is growing more common, particularly among working adults. A cost-effective and natural solution that an increasing number of families are beginning to use is cucumber juice, which is believed to possess qualities that can help lower blood pressure. This study aims to evaluate the effectiveness of cucumber juice in reducing blood pressure by looking at the latest scientific research. A thorough review of available studies was carried out by gathering articles from sites such as Google Scholar, PubMed, and Garuda, utilizing pertinent search terms from 2019 to 2024. The findings indicate that drinking cucumber juice (150–200 mL) daily for a period of 5 to 7 days resulted in significant decreases in both systolic and diastolic blood pressure, especially in individuals with prehypertension or mild hypertension. These advantages are attributed to the high potassium and magnesium content in cucumbers, along with their natural diuretic effects. In a home setting, cucumber juice is regarded as a safe, affordable, and convenient alternative treatment. In conclusion, cucumber juice is viewed as an effective option for managing blood pressure, particularly in attempts to enhance family health